2016
DOI: 10.1016/j.sbi.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the crucial interactions between Cytochrome P450s and non-ribosomal peptide synthetases during glycopeptide antibiotic biosynthesis

Abstract: The importance of Cytochrome P450-catalyzed modifications of natural products produced by non-ribosomal peptide synthetase machineries is most apparent during glycopeptide antibiotic biosynthesis: specifically, the formation of essential amino acid side chains crosslinks in the peptide backbone of these clinically relevant antibiotics. These cyclization reactions take place whilst the peptide substrate remains bound to the non-ribosomal peptide synthetase in a process mediated by a conserved domain of previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 42 publications
4
55
0
1
Order By: Relevance
“…4,6,7 Fig. 1 GPA cyclisation in vitro is enabled by diastereomerically pure phenylglycine thioester peptides: teicoplanin seq.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,7 Fig. 1 GPA cyclisation in vitro is enabled by diastereomerically pure phenylglycine thioester peptides: teicoplanin seq.…”
Section: 2mentioning
confidence: 99%
“…6 In all these cases, however, the assessment of enzymatic activity is complicated by the necessity of peptide intermediates to be bound to peptidyl carrier protein (PCP)-domains, which serve as an attachment point for all amino acid and peptide intermediates during NRPS biosynthesis. 1,2,8 The ability to enzymatically load coenzyme A (CoA) substrates onto PCP domains using the promiscuous phosphopantetheinyl transferase Sfp has made a vital contribution to overcome this problem, as it allows biosynthetic steps to be interrogated without complete reconstitution of the NRPS.…”
mentioning
confidence: 99%
“…The most well-known compound class that exhibits multiple aromatic crosslinks that are installed by P450 enzymes are the glycopeptide antibiotics (GPAs), which include the representative examples vancomycin and teicoplanin. [240][241][242][243] The intramolecular cyclisation reactions catalysed by cytochrome P450 enzymes lead to a specic tertiary structure able to bind to the terminal D-Ala-D-Ala motif of the bacterial cell wall precursor lipid II and thereby blocking cell growth. As last-line antibiotics, they are the major treatment against multiresistant gram-positive pathogens like methicillin-resistant Staphylococcus aureus (MRSA).…”
mentioning
confidence: 99%
“…[250][251][252] More recent work has shown that the process of P450 recruitment to the NRPS-bound peptide is more complicated than is the case for PCP-bound amino acids, with GPA biosynthesis relying on the X-domain, a conserved (albeit modied) condensation domain found between the PCP 253 and TE-domains in the nal NRPS module. 243,[254][255][256][257] The X-domain has an interaction interface that specically binds to the Oxy enzymes, with these continually binding to and releasing from the X-domain to ensure that complete crosslinking of the peptide occurs. 254 The X-domain is also required in the majority of cases to support efficient P450-catalysed crosslinking in vitro, with this requirement strictly enforced for OxyA and OxyE that act aer OxyB.…”
mentioning
confidence: 99%
See 1 more Smart Citation